2010
DOI: 10.1068/a41324
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ambiguity: Aboriginal Identity Negotiation in Southwestern Sydney

Abstract: There has been little discussion on urban Indigenous identity in post-settler societies. However, in the scarce works which exist on this issue there are some remarkably common traits. For most Indigenous people, identity has primarily involved kinship ties associated with their perceived place of origin. In the city, Indigenous people encounter other Indigenous people who cannot be identified through kinship ties; in this situation, organizations dealing with Indigenous issues provide ways of connecting nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The discussions span policies and governance (DeVerteuil and Wilson, 2010;Moore et al, 2011;Peters, 2005;2011a), homelessness (Peters, 2012), housing issues (Gagné, 2013;Walker, 2008;Walker and Barcham, 2010), health (Van Herk et al, 2012), settlement patterns (Forrest et al, 2009;Starchenko and Peters, 2008), the lack of community and invisibility (Lawrence, 2004), women and the loss of legally recognized Indigenous rights (Lawrence, 2004;Peters, 2004), and racism (Paradies and Cunningham, 2009). A key issue has been identity and the definition of ethnicity: that is, who constitutes an Indigenous person, and who makes that decision (Lawrence, 2004;Lobo, 2001a;Sissons, 2005;Watson, 2010;Wilson and Peters, 2005;Yamanouchi, 2010). These questions are of primary importance to Indigenous peoples who have attempted to maintain the right to self-define and have challenged definitions imposed by non-Indigenous peoples.…”
Section: Challenges To Understanding Indigenous Identities In a Non-indigenous Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussions span policies and governance (DeVerteuil and Wilson, 2010;Moore et al, 2011;Peters, 2005;2011a), homelessness (Peters, 2012), housing issues (Gagné, 2013;Walker, 2008;Walker and Barcham, 2010), health (Van Herk et al, 2012), settlement patterns (Forrest et al, 2009;Starchenko and Peters, 2008), the lack of community and invisibility (Lawrence, 2004), women and the loss of legally recognized Indigenous rights (Lawrence, 2004;Peters, 2004), and racism (Paradies and Cunningham, 2009). A key issue has been identity and the definition of ethnicity: that is, who constitutes an Indigenous person, and who makes that decision (Lawrence, 2004;Lobo, 2001a;Sissons, 2005;Watson, 2010;Wilson and Peters, 2005;Yamanouchi, 2010). These questions are of primary importance to Indigenous peoples who have attempted to maintain the right to self-define and have challenged definitions imposed by non-Indigenous peoples.…”
Section: Challenges To Understanding Indigenous Identities In a Non-indigenous Environmentmentioning
confidence: 99%
“…Because outsiders do not always see the dynamics of urban Indigenous populations, Indigenous identities cannot be defined by anyone but urban Indigenous people themselves. Recent studies of ethnic minorities, including Indigenous peoples, have also confirmed that self-identification is key to surveys on ethnic minorities, and a lack of self-identification in surveys may affect the reliability of data and the credibility of surveys of stigmatized populations (Krizsán, 2012;Lobo, 2001a;Ringelheim, 2011;Watson, 2014a;Yamanouchi, 2010). To make survey data more credible, ethnic minorities are even encouraged to 'come out' (Ringelheim, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to these representations and their connected material exclusions, have fuelled a need in published research, for challenging the politics of delimiting places for 'races', and other human identities (see Yamanouchi, 2010), including heteronormative accounts of sexual identity and their sites of belonging (Gorman-Murray, 2011;Waitt and Gorman-Murray, 2011;Singham, 2011).…”
Section: Matters Of Citizenship and Nationmentioning
confidence: 99%
“…More recently, a strong interest in the study of Aboriginal identity in major urban centres such as Sydney is emerging (e.g. Everett, 2010;Yamanoguchi, 2010). The research I draw on here involves 60 semi-structured interviews with Aboriginal people residing in Western Sydney, New South Wales and in Shepparton, Victoria.…”
Section: Introductionmentioning
confidence: 99%